ACERCA DE LA DISCORDANCIA ANGULAR ENTRE LAS FORMACIONES GUANDACOL Y TUPE EN LA SIERRA DE MAZ (PROVINCIA DE LA RIOJA) (Ameghiniana, 2013)
Restricted to the northern slope of cerro Punta Colorada, a local episode of deformation of Guandacol Formation strata is here described. On the basis of stratigraphical considerations and the nature of the paleofloristic associations found in both unities, it is shown that the folding age may be placed between Visean and Westaphalian times and might correspond to an orogenic phase of Variscic Movements.